Psychological compatibility of female basketball players as the factor of competitive activity effectiveness übersetzter Titel (DE) - Berezina, L. A.; Bystrova, O. L.; Nemytov, D. N. (The Russian Journal of Physical Education and Sport, 2018)
Annotation. Every year the level of sports results in female basketball increases, technical and biological resources are close to disappear and one of the ways of searching for the reserves is psychic reserves use. One of the most important training process objectives among female basketball players is not only the effectiveness of tactical interactions increase, but also taking into consideration individual-psychological peculiarities of partners during team composition formation. Material. A new approach is offered to training and competitive activity of highly-qualified female basketball players. The experimental methodology is formed, which is based on the complex of individual-psychological and personal peculiarities of female basketball players during team composition formation and which condition the success of playing activity. Research methods: scientific and scientific-methodical literature analysis and systematization, progressive pedagogical experience of basketball trainers summarizing, pedagogical experiment, testing, statistical data handling. Results. The article offers the methodology of basketball team content formation, taking into account psychological compatibility. The content of the methodology provides the following items realization: female basketball players` individual-psychological and personal peculiarities revelation; the character study of female basketball players` combination during interaction in game parts; compatibility criteria revelation between individual-psychological and personal characteristics of the athletes. Conclusion. The results of pedagogical experiment showed the expediency and effectiveness of this methodology application, the use of which provides more integral approach to basketball team content formation and it helped to improve competitive activity indices among qualified female athletes.